Addition of Water Hyacinth Flour to Feed for Sangkuriang Catfish Seed - Adrian S Pane; Yuniarti Koniyo; Juliana Juliana (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the effect of the addition of water hyacinth flour (Eichornia crassipes) on the manufacture of artificial feed on the survival and growth of sangkuriang catfish (Clarias gariepinus) seeds. This study used an experimental method with three treatments and three replications. The testing method is by feeding a number of different doses. The results showed that treatment A had the highest absolute length and weight growth of 1.7 cm and 0.5925g, followed by treatment B of 1.4 cm and 0.4827 g, and the lowest was indicated by treatment C of 1.2 cm and 0.3217 g. While the highest daily length and weight growth in treatment A were 0.14 cm and 0.049 g, treatment B was 0.12 cm and 0.036 g and C were 0.11 cm and 0.027 g. Survival of catfish seeds in all treatments during the study was 100%. Keywords: catfish; sangkuriang; seeds; feed; water hyacinth.